Enhancing human cord blood hematopoietic stem cell engraftment by targeting nuclear hormone receptors. Issue 4 (July 2018) - Guo, Bin; Huang, Xinxin; Broxmeyer, Hal E.
Abstract : Purpose of review: Allogeneic hematopoietic cell transplantation (HCT) is a life-saving therapy for hematological and nonhematological diseases. Cord blood is a source of transplantable hematopoietic stem cells (HSCs), but limited numbers of HSCs in single cord blood units, which may cause delayed neutrophil, platelet, and immune cell reconstitution, is a major problem for efficient transplantation. Ex-vivo expansion and enhanced homing of cord blood HSC may overcome this disadvantage and improve its long-term engraftment. Here, we discuss the role of nuclear hormone receptors signaling in human cord blood HSC engraftment. Recent findings: Antagonizing retinoid acid receptor (RAR) signaling promotes human HSC expansion and increases myeloid cell production. Cord blood CD34 + cells expanded by SR1 promotes efficient myeloid recovery after transplantation compared with control groups, and leads to successful engraftment. Short-term treatment of glucocorticoids enhances homing and long-term engraftment of human HSCs and HPCs in NSG mice. Peroxisome proliferator-activated receptor-γ (PPARγ) antagonism expands human HSCs and HPCs by preventing differentiation and enhancing glucose metabolism. These findings demonstrate that nuclear hormone receptor signaling components might be promising targets for improving human cord blood HCT. Summary: Better understanding of molecular mechanisms underlying human HSC expansion and homing mediated by nuclear hormone receptor signaling pathways will facilitate enhanced HCT efficacy.